AN ANALYSIS OF CONVERSATIONAL IMPLICATURE STRATEGY IN A DRAMA “THE BEAR” BY ANTON CHEKHOVAND ITS APPLICATION IN ELT - Hendra Suryadi; Muslim Muslim (Journal of Languages and Language Teaching, 2019)
This study was aimed at finding analysis of conversational implicature in a drama “the bear” by Anton Chekhov and its application in English language teaching". This research was conducted in a descriptive qualitative method. The source of data is a script of drama, The sampling technique used was purposive for the sample is chosen based on a certain purpose to reach the objective of this research. The data analyzed based on the theory’s Grace (1975), Yule (2005), Levinson (1992), Jacob L. Mey (1998) and Paltridge (2000). And then each Extract was analyzed based on Types and functions of conversational implicature. After that, the real data are displayed using table and particular. Here, the researcher analyzed several applications of conversational implicature in drama. In analyzing the data the researcher finds the idea from the drama that can be used for improving speaking the students in English language teaching. Based on the analysis, the outcome of this study indicated that all Grice’s proposed conversational implicatures applied to the drama entitled “The Bear”. 28 utterances are consisting of 9 types of generalized conversational implicature, 5 types of particularized conversational implicature, 2 functions of self-protections, 6 functions of power and politeness, 3 functions of giving information, 1 function of entertain the audience and 2 functions of lack specific information. The study was enriching the knowledge of conversational implicature for the teachers and students who should be able to improve speaking skill in teaching-learning activity.